2020
DOI: 10.1002/ppul.25162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bronchial obstruction and its reversibility by shape indexes of the flow‐volume loop in asthmatic children

Abstract: Asthma assessment by spirometry is challenging in children as forced expiratory volume in 1 s (FEV1) is frequently normal at baseline. Bronchodilator (BD) reversibility testing may reinforce asthma diagnosis but FEV1 sensitivity in children is controversial. Ventilation inhomogeneity, an early sign of airway obstruction, is described by the upward concavity of the descending limb of the forced expiratory flow-volume loop (FVL), not detected by FEV1. The aim was to test the sensitivity and specificity of FVL sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…On the one hand, the Δ %Pred expression mode permits the comparison of subjects regardless of age and height (in the French study, 1 heights' interquartile were huge in both controls [130-143 cm] and asthmatics [129-138 cm]). 1 On the other hand, the Δ A expression mode correlates with age and height, and changes in FEV 1 (i.e., ΔFEV 1 ) are smaller in short children than in tall ones. 5 The third point implicates the evaluation of BDR via only flows (i.e., FEV 1 and peak expiratory flow).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…On the one hand, the Δ %Pred expression mode permits the comparison of subjects regardless of age and height (in the French study, 1 heights' interquartile were huge in both controls [130-143 cm] and asthmatics [129-138 cm]). 1 On the other hand, the Δ A expression mode correlates with age and height, and changes in FEV 1 (i.e., ΔFEV 1 ) are smaller in short children than in tall ones. 5 The third point implicates the evaluation of BDR via only flows (i.e., FEV 1 and peak expiratory flow).…”
mentioning
confidence: 97%
“…The second point involves the expression mode of the BDR, where the authors considered the percentage change reported to initial value (Δ %Init ). 1 Despite its huge use in clinical practice, the aforementioned expression' mode presents two main weaknesses. 5 First, Δ %Init exhibits size-and sex-bias in evaluating BDR.…”
mentioning
confidence: 99%
See 2 more Smart Citations